Vigils of the saints and the stational liturgy of Milan. Issue 2 (October 2019) - BAILEY, TERENCE
Abstract: Vigils, an important and eventually troublesome component of the cult of the saints, are attested to in the fourth century by Sts Ambrose, Jerome and Augustine. In Gregorian regions nearly all these penitential observances were prohibited by a synod in Rouen in 1231, and have been virtually ignored in the scholarly literature. In the Ambrosian orbit, Vigils remained an extraordinarily important part of the public liturgy until the end of the Middle Ages; however, the treatment of these offices in the Milanese service books presents a confused picture that can only be pieced together with some difficulty. In clarifying the practices of Vigils, certain details are brought to light concerning the two other examples of the external episcopal liturgy of Milan (the three-day Litany in the week following Ascension, and the daily stations at both the ancient baptistries of the city), and even important details about the practices in the cathedrals themselves, practices concerning which the ordinal is silent, ambiguous or even misleading.